2018
DOI: 10.1007/s11605-017-3524-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Lymphadenectomy in Small Bowel Neuroendocrine Tumors: Analysis of the NCDB

Abstract: Small bowel NETs have high rates of nodal metastasis, even in patients with small tumors, and many patients do not undergo lymphadenectomy despite the clear benefit. Lymphadenectomy of eight nodes is optimal to identify N+ patients. Additionally, minimizing metastatic node ratio with complete regional lymphadenectomy is associated with improved survival in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…In the United States, the small intestine is the third most prevalent primary site of NET, following rectum and lung, and NET is the most common neoplasm arising in the small intestine, followed by adenocarcinoma and lymphoma . Ileal NET (i‐NET) accounts for 90% of small intestinal NETs (excluding duodenal origin) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, the small intestine is the third most prevalent primary site of NET, following rectum and lung, and NET is the most common neoplasm arising in the small intestine, followed by adenocarcinoma and lymphoma . Ileal NET (i‐NET) accounts for 90% of small intestinal NETs (excluding duodenal origin) …”
Section: Introductionmentioning
confidence: 99%
“…Because i‐NETs are asymptomatic at an early stage, they are frequently diagnosed at an advanced stage with metastases involving regional lymph node (34%‐88%) and the liver (56%‐78%) . Regional lymphadenopathy is associated with desmoplasia of the mesentery forming a mesenteric mass .…”
Section: Introductionmentioning
confidence: 99%
“…They believe that the best lymph node dissection is not simply a prolonged small bowel resection, but that the classi cation of mesenteric LNs should be standardized to help standardize the management of NET patients. According to Benjamin M Motz's report 21 , about 20% of patients with small bowel cancer resection from The National Cancer Database have not received lymph node dissection, although this can bring some benign effects.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons must be informed that lymphadenectomy is always required in SI-NET surgery. Retrospective registry analyses have suggested that at least 8 (or possibly 12) removed lymph nodes are needed to improve overall survival [7][8][9]. Moreover, French guidelines have suggested discussing a 're-intervention' after postoperative evaluation by FDOPA-PET or 68 Ga-PET if fewer than 8 lymph nodes have been resected [25].…”
Section: Surgery Of Mlnmmentioning
confidence: 99%
“…SI-NET primary tumors are usually small (<20 mm), distal in the ileum, and multiple in 30% to 50% of cases [ 4 , 5 , 6 ]. Mesenteric lymph node metastases (MLNM) are present in more than 80% of patients at diagnosis, regardless of the size of the primary tumor [ 7 , 8 , 9 , 10 , 11 ]. MLNM are typically larger than primary tumors and associated with dense desmoplastic fibrosis leading to retractile mesenteritis.…”
Section: Introductionmentioning
confidence: 99%